Potensi Tepung Ubi Jalar Ungu (Ipomea batatas L.) dalam Pembuatan Bolu Kemojo sebagai Makanan Khas Provinsi Riau - Syahli Putra Turelanda (Jurnal Teknologi dan Industri Pertanian Indonesia, 2016)
(Effect Potential Use of Purple Sweet Potato Flour ss Ingredient in Kemojo Cake, Riau Province Traditional Food) ABSTRACT. The purpose of this study was to obtain an optimal ratio of purple sweet potato flour to wheat flour to produce good quality kemojo cake product. This study uses a completely randomized design (CDR) completely randomized design (CRD) with five treatment. The analyzed of kemojo cake includes moisture content, ash content, protein content, sucrose content and sensory assessment. The result showed that  kemojo cake best treatment is TUJ2 with moisture content of 24.32%, ash content of 0.80%, protein content of 13.25%, sucrose content of 21.82% and descriptive sensory showed light purple colour (score 2.80), a hint of sweet potato flavour (score 3.00), a little bit of purple sweet potato scent (score 3.03), the chewy texture (score 3.00) and panelist favored overall (score 2.06).